DNA fragmentation of lymphocytes and sperm cells induced by nickel released from orthodontic archwires: A preliminary study - MARTÍNEZ, Raúl Uriel MEDINA; MARTÍNEZ, Javier MORÁN; Roberto BELTRAN DEL RIO PARRA; LUNA, Pedro IV GONZÁLEZ; UMAÑA, José Alfredo FACIO; MARTÍNEZ, Nadia BETANCOURT (Dental Materials Journal, 2024)
Orthodontic brackets and archwires placed intraorally are subject to corrosion, leading to the release of cytotoxic metal ions. The aim of this study was to determine whether the use of orthodontic NiTi archwires increases systemic Ni levels and cause alterations on the DNA of cells unrelated to the oral environment such as lymphocytes and sperm cells. Human urine, semen and blood samples were collected before (baseline) sham placement of orthodontic archwires and 15 and 30 days after placement. Lymphocytes and sperm cells cells were evaluated by comet assay. Ni concentration levels in urine increased significantly between baseline and 15 days (p<0.01) and 15 and 30 days of exposure (p<0.01). Progressive decrease in sperm viability and motility was observed between the sampling periods. Lymphocytes and sperm cells showed DNA fragmentation. The increase in systemic concentration of nickel induced structural damage in the DNA of lymphocytes and human sperm cells.